2021
DOI: 10.1039/d1ra03659a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable structural and optical properties of CuInS2 colloidal quantum dots as photovoltaic absorbers

Abstract: We report the facile hot-injection colloidal synthesis of near-stoichiometric CuInS2 quantum dots at varying reaction times and temperatures which exhibit both optical and structural tunability with implications for enhanced photovoltaic utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 51 publications
4
11
2
Order By: Relevance
“…Similar outcomes reported by Xie and co-workers 76 showed that a gradual increase in particle growth temperature induced transformation from primarily wurtzite to chalcopyrite phases. Therefore, as in our previous report, 13 we suggest that formation of wurtzite Ag:CIS in this case likely proceeds via a wurtzite phase Ag:Cu 2 S intermediate, Ag x Cu 2Àx S, since the soft Lewis acid ions, Ag + and Cu + would proportionally coordinate with the dodecanethiol ligand, a soft Lewis base. Subsequent decomposition of this in situ complex to Ag x Cu 2Àx S nanoparticles is followed by cationic exchange with In 3+ to form Ag x Cu y InS 2 QDs stabilized by the capping ligand.…”
Section: Formation Mechanism and Phase Transformationsupporting
confidence: 85%
See 4 more Smart Citations
“…Similar outcomes reported by Xie and co-workers 76 showed that a gradual increase in particle growth temperature induced transformation from primarily wurtzite to chalcopyrite phases. Therefore, as in our previous report, 13 we suggest that formation of wurtzite Ag:CIS in this case likely proceeds via a wurtzite phase Ag:Cu 2 S intermediate, Ag x Cu 2Àx S, since the soft Lewis acid ions, Ag + and Cu + would proportionally coordinate with the dodecanethiol ligand, a soft Lewis base. Subsequent decomposition of this in situ complex to Ag x Cu 2Àx S nanoparticles is followed by cationic exchange with In 3+ to form Ag x Cu y InS 2 QDs stabilized by the capping ligand.…”
Section: Formation Mechanism and Phase Transformationsupporting
confidence: 85%
“…12 In particular, CIS is of interest as its optoelectronic properties can be tuned solely by intrinsic lattice defects due to the large range of anion and cation off-stoichiometry tolerance. 13 Congruent with other reports involving the defect chemistry of CIS, 14,15 recently we reported various intrinsic defect states implicated in the broad photoluminescence emission of slightly off-stoichiometric undoped CIS QDs. 13 Since shallow energy states from some of these defects act as trapping states suppressing conductivity and overall power conversion efficiency (PCE) of CIS-based solar cells, 16 it has been shown that strategic doping and alloying are useful in tailoring their morphological, optical and electrical properties, 3,9,10 for more spectrally adaptive thin film and quantum dot solar cells.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations